La adquisición de los recursos gramaticales de referencia por estudiantes de español como segunda lengua en el nivel principiante - Vargas Víquez, Silvia (2013)
They are presented in this article the analysis results of a corpus written by Anglophone learners of the beginner level of Spanish. These findings are part of a larger investigation that seeks to determine if there is a pattern of acquisition of referential grammatical resources in Spanish as a second language (common noun with indefinite determinant, common substantive with defined determinant, proper name, third-person singular pronoun and their possessive determiners, zero anaphora).